2017
DOI: 10.1167/17.5.19
|View full text |Cite
|
Sign up to set email alerts
|

The perception of hazy gloss

Abstract: Most previous work on gloss perception has examined the strength and sharpness of specular reflections in simple bidirectional reflectance distribution functions (BRDFs) having a single specular component. However, BRDFs can be substantially more complex and it is interesting to ask how many additional perceptual dimensions there could be in the visual representation of surface reflectance qualities. To address this, we tested materials with two specular components that elicit an impression of hazy gloss. Stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 45 publications
0
24
1
Order By: Relevance
“…One may want to use two different types of functions, but this would complicate the peak ratio formula p without adding much more expressivity to the model. We have also limited our composite BRDF to a pair of components to be in accordance with existing perceptual studies on hazy gloss [VBF17]. Adding a third component would bring two additional degrees of freedom, but it is not clear how they might affect perception: would the new component be perceived independently or as part of the halo?…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 4 more Smart Citations
“…One may want to use two different types of functions, but this would complicate the peak ratio formula p without adding much more expressivity to the model. We have also limited our composite BRDF to a pair of components to be in accordance with existing perceptual studies on hazy gloss [VBF17]. Adding a third component would bring two additional degrees of freedom, but it is not clear how they might affect perception: would the new component be perceived independently or as part of the halo?…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Vangorp et al [VBF17] have suggested that the perception of hazy gloss relies on a decomposition of the specular BRDF into a specular core and a surrounding halo. In particular, they show that the energy of their halo component is strongly correlated to subjective haziness ratings obtained through a perceptual experiment.…”
Section: Hazy Gloss Modelmentioning
confidence: 99%
See 3 more Smart Citations